Glutathione: new roles in redox signaling for an old antioxidant - Aquilano, Katia; Baldelli, Sara; Ciriolo, Maria R. (Frontiers in Pharmacology, 2014)
The physiological roles played by the tripeptide glutathione have greatly advanced over the past decades superimposing the research on free radicals, oxidative stress and, more recently, redox signalling. In particular, GSH is involved in nutrient metabolism, antioxidant defence and regulation of cellular metabolic functions ranging from gene expression, DNA and protein synthesis to signal transduction, cell proliferation and apoptosis. This review will be focused on the role of GSH in cell signalling by analysing the more recent advancements about its capability to modulate nitroxidative stress, autophagy and viral infection.